2015
DOI: 10.2169/internalmedicine.54.2332
|View full text |Cite
|
Sign up to set email alerts
|

Late Onset Post-Transfusion Hepatitis E Developing during Chemotherapy for Acute Promyelocytic Leukemia

Abstract: We herein report the case of a leukemia patient who developed hepatitis E seven months after undergoing a transfusion with contaminated blood products. The latency period in this case was significantly longer than that of typical hepatitis E. Recently, chronic infection with hepatitis E virus (HEV) genotype 3 has been reported in immunocompromised patients. There is a possibility that our patient was unable to eliminate the virus due to immunosuppression following chemotherapy and the administration of steroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Additionally, donor screening of five of the six involved donations revealed no HEV RNA ( 6 ). In Japan, seven further posttransfusion hepatitis E cases (six cases of RBC transfusion, one case of PC transfusion) were detected, according to the official announcement of the Japanese Red Cross Society, but no information on either donor or patient antibody status or the infectious dose were available ( 26 ). The German authorities also announced four further posttransfusion hepatitis E cases (two RBC, two PC) in their actual hemovigilance report so far, without detailed case information ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, donor screening of five of the six involved donations revealed no HEV RNA ( 6 ). In Japan, seven further posttransfusion hepatitis E cases (six cases of RBC transfusion, one case of PC transfusion) were detected, according to the official announcement of the Japanese Red Cross Society, but no information on either donor or patient antibody status or the infectious dose were available ( 26 ). The German authorities also announced four further posttransfusion hepatitis E cases (two RBC, two PC) in their actual hemovigilance report so far, without detailed case information ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hewitt and colleagues showed that the risk relied on the type of blood product ranging from 25% for RBCs, 50% for platelets, and 100% for fresh‐frozen plasma. It should be noted that the majority of posttransfusional acute hepatitis E cases have been reported in immunosuppressed patients, with a low number of reports in immunocompetent subjects …”
Section: Discussionmentioning
confidence: 99%
“…HEV‐gt‐3 has been investigated among blood donors in several western countries, with a prevalence ranging from 0.01% to 0.13% . Transmission of HEV‐gt‐3 from blood components has been described in the United Kingdom, France, and Japan . Most studies examining the prevalence of blood donor‐related HEV are based on initially pooled donor samples and thus are biased toward detection of donors with higher viral loads.…”
mentioning
confidence: 99%
“…2,[9][10][11][12][13][14][15] Transmission of HEV-gt-3 from blood components has been described in the United Kingdom, France, and Japan. 12,[16][17][18][19] Most studies examining the prevalence of blood donor-related HEV are based on initially pooled donor samples and thus are biased toward detection of donors with higher viral loads. As a result, underestimation of the true prevalence of HEV is likely.…”
mentioning
confidence: 99%